(3GdajM GdbSi aj GdaJM GdbOSis - (3eMeO Hf eMeO MGeO GdCUHgGfj, YeGO GdOjf GdcGJH,J (B597 (3g` s
(3ChdgG (B:s
(3fSCd Gddg ef GdMeO eG jHdZ bVGA Mbg s
(3BNQgG (B:s
(3jfJgi HPcQ QMjd GdCaQfL UhH YSbdGf hBNQ GdehLhO efg bhdg (B: (3WQM efge hLQM cKjQ Shi ef CNP agh GdCf CSjQ s
(3jTJed GdeNWhW Ydi CMOGK ef (B583 (3Edi SfI (B587s
(3cJHJ ai YUQ GdeDda ef JMHjS GdSdWGf CHj GdYHGS GdefUhQ HGddg Ydi LGeY GdbQhjjf YGe (B1001 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B26s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs